Genetic and physiological relationships between L-asparaginase I and asparaginase II in Saccharomyces cerevisiae. - Jones, G E (1977)
The cistron that codes for L-asparaginase I in Saccharomyces cerevisiae (aspl) is not genetically linked to either of the cistrons coding for expression of asparaginase II (asp2 and asp3). Cells containing different combinations of theses enzymes grow at different rates in media in which L-asparagine or D-asparagine is the only source of nitrogen for cell replication. Cells lacking L-asparaginase I but possessing asparaginase II grow more rapidly in medium containing D-asparagine as a nitrogen source than cells containing both enzymes, even though D-asparagine is not a substrate of L-asparaginase I. These results indicate that L-asparaginase I and asparaginase II interact in some way to regulate the utilization of asparagine as a nitrogen source for cell growth.